De novo Genome Assembly and Single Nucleotide Variations for Soybean Mosaic Virus Using Soybean Seed Transcriptome Data - Yeonhwa Jo; Hoseong Choi; Miah Bae; Sang-Min Kim; Sun-Lim Kim; Bong Choon Lee; Won Kyong Cho; Kook-Hyung Kim (The Plant Pathology Journal, 2017)
Soybean is the most important legume crop in the world. Several diseases in soybean lead to serious yield losses in major soybean-producing countries. Moreover, soybean can be infected by diverse viruses. Recently, we carried out a large-scale screening to identify viruses infecting soybean using available soybean transcriptome data. Of the screened transcriptomes, a soybean transcriptome for soybean seed development analysis contains several virus-associated sequences. In this study, we identified five viruses, including soybean mosaic virus (SMV), infecting soybean by de novo transcriptome assembly followed by blast search. We assembled a nearly complete consensus genome sequence of SMV China using transcriptome data. Based on phylogenetic analysis, the consensus genome sequence of SMV China was closely related to SMV isolates from South Korea. We examined single nucleotide variations (SNVs) for SMVs in the soybean seed transcriptome revealing 780 SNVs, which were evenly distributed on the SMV genome. Four SNVs, C-U, U-C, A-G, and G-A, were frequently identified. This result demonstrated the quasispecies variation of the SMV genome. Taken together, this study carried out bioinformatics analyses to identify viruses using soybean transcriptome data. In addition, we demonstrated the application of soybean transcriptome data for virus genome assembly and SNV analysis.